383 LAPAROSCOPIC CREATION OF RETROSTERNAL ROUTE FOR GASTRIC CONDUIT RECONSTRUCTION; SAFE AND FEASIBLE PROCEDURE. (17th September 2021) - Horikawa, Manabu; Oshikiri, Taro; Kitamura, Yu; Horie, Kazumasa; Takiguchi, Gosuke; Urakawa, Naoki; Hasegawa, Hiroshi; Yamamoto, Masashi; Kanaji, Shingo; Matsuda, Yoshiko; Yamashita, Kimihiro; Matsuda, Takeru; et al.
Abstract: : Reconstruction routes after esophagectomy include posterior mediastinal, retrosternal, and subcutaneous route. We have performed posterior mediastinal reconstruction, but this route has higher risks of gastro-tracheal fistula and hiatal hernia. To avoid these complications, now we take the retrosternal route as our first choice by creating the route laparoscopically before pulling-up gastric conduit. We report the successful and safe procedure. Methods: We performed laparoscopic creation of retrosternal route in 13 thoracoscopic/robot-assisted minimally invasive esophagectomies since August 2019. In practice, a peritoneal incision at the dorsal side of the xiphoid process is started. Then, via 12 mm port on the surgeon's right hand inserted slightly to the right and cranial side of the umbilical camera port, we dissect loose connective tissues from the caudal side to the cranial side behind the sternum and inside the internal thoracic vessels as landmarks. The time required to create the route and pleural injury rate during the procedure was examined. Results: Thirteen cases were divided into two groups as early period group (seven cases) and later period group (six cases) respectively. The time required for route creation was 31.3 minutes(average) in the early period group, and 16.7 minutes in the later period group. There is tendency towards faster in later period group than in earlier one. The overall pleural injury rate was 15% (2 of 13 cases). Although it was difficult to determine the amount of bleeding, it was visually observed that the bleeding during the route creation was lower in the later period group than in the early period group. Conclusion: The entire laparoscopic procedure to create retrosternal route makes it easier to observe and preserve the pleura and internal thoracic vessels compared to blind blunt dissection. As a conclusion, laparoscopic creation of retrosternal route for gastric conduit reconstruction is safe and feasible with good learning curve. Video: https://www.dropbox.com/sh/p0wc3x46n33jp23/AADwiWHYIEUNUX6qZsERVIOga?dl=0 .